A new snake of the genus Hebius (Serpentes: Natricidae) from the Ngoc Linh Mountain Range, Vietnam - Le, Manh Van; Phan, Khanh Duy; Nguyen, Thanh Luan; Murphy, Robert W.; Lam, Ngon Quang; Nguyen, Sang Ngoc; Che, Jing (Zootaxa, 2026)
We describe a new keelback snake of the genus Hebius from the Ngoc Linh Mountain Range, Central Highlands, Vietnam, based on morphological characters and molecular evidence (Cytb). Hebius ngoclinhensis sp. nov. is diagnosed by the following combination of morphological features: dorsal scale rows 19-19-17; first dorsal scale row smooth; ventrals 143–148; subcaudals 95–97, paired; two preoculars; two or three postoculars; one loreal; eight or nine supralabials; ten infralabials; cloacal plate divided; maxillary teeth 24–26, gradually enlarged, with two distinctly enlarged teeth posteriorly; 17 keeled dorsal scale rows at midbody; dorsal surface of body and tail dark brown with numerous irregular dark yellow spots; a distinct reddish-brown dorsolateral stripe on the 4th–7th dorsal scale rows on each side; ventral surface of body and tail reddish-orange to orange; and lateral margins of ventrals and subcaudals dark brown. In addition, the new species differs from its congeners by an uncorrected p-distance in Cytb sequences of at least 9.3%.